Apigenin role against thioacetamide-triggered liver fibrosis: Deciphering the PPARγ/TGF-β1/NF-κB and the HIF/FAK/AKT pathways - Rehab Fawzy Abdel-Rahman; Hany M Fayed; Marwan A Mohamed; Alyaa F Hessin; Gihan F Asaad; Sahar S AbdelRahman; Abeer A Salama; Mahmoud S Arbid; Hanan A Ogaly (Journal of HerbMed Pharmacology, 2023)
Introduction: Liver tissue malfunction is a severe worldwide health concern that arises from various chronic liver conditions. The goal of this investigation was to look into the anti-fibrotic effect of apigenin (APG), an antioxidant found in various plants, versus thioacetamide (TAA)-triggered hepatic scarring in rats and the potential mechanisms behind it. Methods: TAA was administered thrice weekly (100 mg/kg, i.p.) for two weeks to produce hepatic scarring. APG was administered after TAA for 14 days (5 or 10 mg/kg, orally). Thereafter, hepatic liver enzymes, inflammatory markers, fibrotic indicators, and histopathological changes were evaluated. Results: TAA increased the activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), reduced albumin and total protein, elevated hepatic level of lipid peroxidation, focal adhesion kinase (FAK), hypoxia-inducible factor-1α (HIF-1α), and inflammatory cytokines, decreased interleukin-10 (IL-10), reduced hepatic expression of peroxisome proliferator-activated receptor gamma (PPARγ) and nuclear factor-erythroid factor 2-related factor 2 (Nrf2), and elevated serine-threonine protein kinase (AKT) expression. Furthermore, TAA increased hepatic contents of collagen I, connective tissue growth factor (CTGF), hydroxyproline, and alpha-smooth muscle actin. On the other hand, APG evaded these changes and mitigated the harmful effects of TAA in a dose-dependent way. Histopathological and immunohistochemical observations reinforced these biochemical outcomes. Conclusion: APG can potentially alleviate liver fibrosis mediated via FAK and HIF1 inhibiting signaling pathways.